Strategic challenges in upgrading the population’s health in the transition countries of South Eastern Europe (Italian Journal of Public Health, 2009)
Since the devastating nineties of the last century a slow but steady improvement of the living conditions in the region of South Eastern Europe (SEE) has be observed. However, so far only three countries, i.e. Bulgaria, Romania and Slovenia, have managed to ascent to the European Union and only Slovenia has joined the European currency. All others are still struggling with a difficult heritage of inappropriate vertical management structures, overstaffing and outmigration of the well educated young. This résumé applies also to the field of public health where, for example, the old hygienic tradition remained dominant, often maintaining huge laboratory facilities in the institutes of public health and very small numbers of staff being allocated to health promotion and modern participative management. This situation cannot be overcome easily nor in short term. Supported by funds from the German contribution to the European Stability Pact, the Forum for Public Health in South Eastern Europe (FPH-SEE: www.snz.hr/fphsee) has established a permanent collaboration between the public health institutions in the region, including foremost the Schools of Public Health (SPH), the National Public Health Associations (PHA) and some national Institutes of Public Health (IPH).